PENGEMBANGAN LKPD BERBASIS MEMBACA DENGAN METODE CIRC BERBANTUAN CD INTERAKTIF MATERI SEGIEMPAT - Lukmanul Akhsani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2013)
Student needs a help service study that gets to help increase their studying achievement. The research was aimed to: (1) valid student work sheet with reading basis of quadrangle by using CIRC (Cooperative Integrated Reading and Composition) method; (2) measure the effectiveness of the learning material which used student work sheet with reading basis for teaching quadrangle in seven graders by using circ method; (3) describing practicality by used student work sheet with reading basis for teaching quadrangle in seven graders by using CIRC. This type of research used model of 4-D which consisted of the phase of preliminary investigation, the phase of define, design, develop, and disseminate. But, in this reaserch just until phase of develop. It has also been developed student worksheet. The subjects of the research were the seventh graders, with Clutser Sampling, gotten two classes which is the experiment class and control class. The research data were collected from (1) validation sheet; (2) Observation sheet; (3) questionnaire, and (4) the test. The results showed (1) student work sheet developed have been declared valid by the validator with an average score of 3,4 from supreme scores 4, (2) teacher ability observation result gotten 3,6 of supreme scores 4 and student response are gotten 87% one mean developed tool practical; (3) result from experiment showed the average achievement of those trial class which performed better than those of control class. Base explanation upon, concluded that the development of student work sheet with reading basis for teaching quadrangle in seven graders by using CIRC accomplishes valid tools, practical purpose and effective learning. So, Development student work sheet be reached.